Change of Air Quality of Bursa City in Time - (:unkn) unknown (MARMARA UNIV, 2017)
Air pollution is a situation that threatens the living and nonliving environments. Effects of that pollution involve not only in our days but also in next generations. The purpose of the study is that evaluating the causes of the air pollution problem which is increasing rapidly in the cities and the physical geographical factors affecting the air pollution. In addition, the variation of air quality of Bursa City examines in time. First of all, Bursa City air quality data between the years of 1990 - 2007 was obtained from the Ministry of Health Air Quality measurements through TUIK. The data between the years of 2007-2011, data was provided from Ministry of Environment and Urbanization Air Quality again via TUIK. The data between the years of 2011-2016 was procured through the National Air Quality Monitoring Network system of the Ministry of Environment and Urbanization. As a result of the study, the particulate matter ratios exceeded the prescribed limit values in recent years. Between 1990 and 2008, it was observed that the concentrations of particulate matter, which declined over time due to fuel quality controls, but between the years of 2008 and 2016 increased. Sulfur dioxide ratios were high at the beginning of the 90s and from the 2000s it does not exceed the anticipated limit values.
Keywords: Air pollution; Bursa city; particulate matter; sulphur dioxide